Punicalagin, a pomegranate polyphenol sensitizes the activity of antibiotics against three MDR pathogens of the Enterobacteriaceae - Saba Kiran; Anam Tariq; Shoaib Iqbal; Zubera Naseem; Waqar Siddique; Sobia Jabeen; Rizwan Bashir; Ashfaq Hussain; Moazur Rahman; Fazal-e Habib; Waqar Rauf; Aamir Ali; et al. (BMC, 2024)
Abstract Background Multidrug resistance (MDR) in the family Enterobacteriaceae is a perniciously increasing threat to global health security. The discovery of new antimicrobials having the reversing drug resistance potential may contribute to augment and revive the antibiotic arsenal in hand. This study aimed to explore the anti-Enterobacteriaceae capability of bioactive polyphenols from Punica granatum (P. granatum) and their co-action with antibiotics against clinical isolates of Enterobacteriaceae predominantly prevalent in South Asian countries. Methods The Kandhari P. granatum (Pakistani origin) extracts were tested for anti-Enterobacteriaceae activity by agar well diffusion assay against MDR Salmonella enterica serovar Typhi, serovar Typhimurium and Escherichia coli. Predominant compounds of active extract were determined by mass spectrometry and screened for bioactivity by agar well diffusion and minimum inhibitory concentration (MIC) assay. The active punicalagin was further evaluated at sub-inhibitory concentrations (SICs) for coactivity with nine conventional antimicrobials using a disc diffusion assay followed by time-kill experiments that proceeded with SICs of punicalagin and antimicrobials. Results Among all P. granatum crude extracts, pomegranate peel methanol extract showed the largest inhibition zones of 25, 22 and 19 mm, and the MICs as 3.9, 7.8 and 7.8 mg/mL for S. typhi, S. typhimurium and E. coli, respectively. Punicalagin and ellagic acid were determined as predominant compounds by mass spectrometry. In plate assay, punicalagin (10 mg/mL) was active with hazy inhibition zones of 17, 14, and 13 mm against S. typhi, S. typhimurium and E. coli, respectively. However, in broth dilution assay punicalagin showed no MIC up to 10 mg/mL. The SICs 30 μg, 100 μg, and 500 μg of punicalagin combined with antimicrobials i.e., aminoglycoside, β-lactam, and fluoroquinolone act in synergy against MDR strains with % increase in inhibition zone values varying from 3.4 ± 2.7% to 73.8 ± 8.4%. In time-kill curves, a significant decrease in cell density was observed with the SICs of antimicrobials/punicalagin (0.03-60 μg/mL/30, 100, 500 μg/mL of punicalagin) combinations. Conclusions The P. granatum peel methanol extract exhibited antimicrobial activity against MDR Enterobacteriaceae pathogens. Punicalagin, the bacteriostatic flavonoid act as a concentration-dependent sensitizing agent for antimicrobials against Enterobacteriaceae. Our findings for the therapeutic punicalagin-antimicrobial combination prompt further evaluation of punicalagin as a potent activator for drugs, which otherwise remain less or inactive against MDR strains.